Lispro administered by the QS-M Needle-Free Jet Injector generates an earlier insulin exposure. (1st September 2016) - Hu, Jinbo; Shi, Hui; Zhao, Changhong; Li, Xiyue; Wang, Yue; Cheng, Qingfeng; Goswami, Richa; Zhen, Qianna; Mei, Mei; Song, Ying; Yang, Shumin; Li, Qifu
ABSTRACT: Objective : The aim of this study is to evaluate the pharmacokinetic and pharmacodynamic (PK-PD) profiles of lispro administered by the QS-M needle-free jet injector in Chinese subjects. Research design and methods : A randomized, double-blind, double-dummy, cross-over study was performed. Eighteen healthy volunteers were recruited. Lispro (0.2 units/kg) was administered by the QS-M needle-free jet injector or by conventional pen. Seven-hour euglycemic clamp tests were performed. Results : A larger area under the curve (AUCs) of insulin concentration and glucose infusion rate (GIR) during the first 20 minutes after lispro injection by the jet injector compared to the insulin pen was observed (24.91 ± 15.25 vs. 12.52 ± 7.60 mg. kg −1, P < 0.001 for AUCGIR, 0–20 min ; 0.36 ± 0.24 vs. 0.10 ± 0.04 U min L −1, P < 0.001 for AUCINS, 0–20 min ). Needle-free injection showed a shorter time to reach maximum insulin concentration (37.78 ± 11.14 vs. 80.56 ± 37.18 min, P < 0.001) and GIR (73.24 ± 29.89 vs. 116.18 ± 51.89 min, P = 0.006). There were no differences in total insulin exposure and hypoglycemic effects between the two devices. Conclusion : Lispro administered by QS-M needle-free injector results in earlier and higher insulin exposure than conventional pen, and a greater early glucose-lowering effect with similar overall potency.